Comparison of the Legal Consequences of Mixed Marriages with and without a Marriage Agreement - Lakeisha, Hilarry (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Marriage is a profound and multifaceted bond, encompassing both physical and spiritual dimensions, between a man and a woman, which serves as the cornerstone of family life and social stability. In contemporary Indonesia, globalization and increasing cross-cultural interactions have led to a rise in marriages between Indonesian citizens and foreign nationals, commonly referred to as mixed marriages. Despite this growing trend, many couples enter into such unions without establishing a prenuptial agreement, often due to limited awareness of the legal implications and protections available under Indonesian law. The absence of a prenuptial agreement in mixed marriages can result in complex legal challenges, particularly regarding the ownership, management, and division of marital property, inheritance rights, and the ability of Indonesian citizens to retain legal ownership of property, such as land, that may be restricted for foreigners. This paper examines and compares the legal outcomes of mixed marriages conducted with and without prenuptial agreements, drawing upon Indonesian Civil Law, the Marriage Law (UU No. 1 Tahun 1974), the Agrarian Law (UUPA), and relevant judicial decisions including the Constitutional Court ruling No. 69/PUU-XIII/2015. The study highlights how prenuptial agreements can provide legal certainty, protect property rights, prevent disputes, and ensure fair and equitable treatment for both spouses. By analysing these differences, this research offers valuable insights for couples, notaries, and legal practitioners navigating the increasingly complex legal landscape of mixed marriages in Indonesia, and emphasizes the critical importance of legal awareness and proactive planning in family law matters.